The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s13072-023-00485-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovulatory signal-triggered chromatin remodeling in ovarian granulosa cells by HDAC2 phosphorylation activation-mediated histone deacetylation

Abstract: Background Epigenetic reprogramming is involved in luteinizing hormone (LH)-induced ovulation; however, the underlying mechanisms are largely unknown. Results We here observed a rapid histone deacetylation process between two waves of active transcription mediated by the follicle-stimulating hormone (FSH) and the LH congener human chorionic gonadotropin (hCG), respectively. Analysis of the genome-wide H3K27Ac distribution in hCG-treated granulosa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Likewise, the list of granulosa-specific genes included canonical marker genes HSD17B1, INHBB, FOXL2, and AMH and the recently reported TNNI3, MAGED2, CD99, SERPINE2, CDH2, and BEX1 (9, 13), along with many histone protein-coding genes (data S5), which have not been reported for granulosa cells. However, numerous studies have suggested that proliferating granulosa cells undergo large-scale epigenetic change during late folliculogenesis, partly driven by gonadotrophins such FSH (40)(41)(42)(43). The list also included genes involved in granulosa cell-oocyte signaling, such as the transzonal projection-related genes FSCN1 and MYO10, and the tetraspanin protein gene TSPAN7, which is involved in extracellular vesiclemediated signaling between granulosa cells and the oocyte (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the list of granulosa-specific genes included canonical marker genes HSD17B1, INHBB, FOXL2, and AMH and the recently reported TNNI3, MAGED2, CD99, SERPINE2, CDH2, and BEX1 (9, 13), along with many histone protein-coding genes (data S5), which have not been reported for granulosa cells. However, numerous studies have suggested that proliferating granulosa cells undergo large-scale epigenetic change during late folliculogenesis, partly driven by gonadotrophins such FSH (40)(41)(42)(43). The list also included genes involved in granulosa cell-oocyte signaling, such as the transzonal projection-related genes FSCN1 and MYO10, and the tetraspanin protein gene TSPAN7, which is involved in extracellular vesiclemediated signaling between granulosa cells and the oocyte (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Target enrichment ROIs were segmented into AOIs based on staining for CD68, Ki67, SMA, DAZL, and PGR. To collect concentric ROIs from ovarian follicles, a mask was designed in ImageJ (40) and imposed on the follicle's region in the tissue.…”
Section: Nanostring Library Preparation and Sequencingmentioning
confidence: 99%